Factors associated with the family reintegration stability for children with a residential care experience in Ghana. Issue 1 (March 2022) - Frimpong-Manso, Kwabena; Agbadi, Pascal; Deliege, Antoine
There is limited evidence on family reintegration for children who have been in residential care within the African context. The goal of this study is to find out what factors impact reintegrated institutionalized children's desire to remain with their biological parents or extended family. The dataset included records for 659 interviewed children and their guardians. However, the analyses were limited to 408 cases with complete data on the dependent and independent variables. Most of the children in the study (73%) preferred to remain with their relatives. The age of the child, length of time spent in residential care, and having a case file, were all factors linked to the children's wish to stay with their family. Based on the findings of the study, social workers should do a full assessment and documentation to decide if reintegration is appropriate, prepare the child and family, and give follow-up assistance to ensure stable reintegration. Social workers must also link reunified families to long-term support such as enrollment on the Livelihood Empowerment against Poverty social protection program, and they should monitor placements to improve the stability of the reintegration.